2020
DOI: 10.20944/preprints202010.0241.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determination of Tractor Engine Oil Change Interval Based on Material Properties

Abstract: This article focuses on the issue of motor oils used in the engines of off-road mobile machinery (NRMM), more specifically tractors. The primary goal of the paper is to determine the appropriate replacement interval for these oils. The physical properties of the examined samples were first determined by conventional instruments. Furthermore, the concentration of abrasive metals, contaminants, and additive elements were measured using an optical emission spectrometer. Lastly, the content of water, fuel, glycol,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…(Zając et al, 2015), who tested tractors with different mileages, reported that the Fe content was 16.5-267 ppm, Cu 5.85-11.75 ppm and Pb 1.42-13.7 ppm. The analyzes of Cr, Ni Pb, Fe by (Gołębiowski et al, 2018;Wolak et al, 2018;Hönig et al, 2020) showed a similar nature of oil changes in the engine with increased mileage.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…(Zając et al, 2015), who tested tractors with different mileages, reported that the Fe content was 16.5-267 ppm, Cu 5.85-11.75 ppm and Pb 1.42-13.7 ppm. The analyzes of Cr, Ni Pb, Fe by (Gołębiowski et al, 2018;Wolak et al, 2018;Hönig et al, 2020) showed a similar nature of oil changes in the engine with increased mileage.…”
Section: Resultsmentioning
confidence: 88%
“…The increase in Cu content could indicate an increase in wear of one of the plain bearings (Hönig et al, 2020). The highest increase in Cu content was found during work with the cultivator (150%).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations